TYPES AND FUNCTIONS OF FILLERS USED BY THE FEMALE TEACHER AND LECTURER IN SURABAYA - Valantino A Pamolango (Universitas 17 Agustus 1945 Surabaya, 2015)
Abstract. This research deals with the production of fillers used by teacher and lecturer in the teaching process. The study involved two subjects: one female teacher and one female lecturer in Surabaya. The problems to be examined in the study were the types, the frequency of occurrences and the functions of fillers used by the two subjects. In the study, the writer mainly adopted Roseâ€™s (1998) theory on the types of fillers, combined with similar notions on the types and functions of fillers from StenstrÃ¶m (1994) and Baalen (2001). The the study adopts a descriptive qualitative approach, focusing on the types and the functions of fillers. As the source of data, the writer took two class meetings, in which each teaching process was done by the two subjects. In the data analysis, the writer found that the female lecturer produces fewer fillers than the female teacher. The female teacher produced 346 fillers in the teaching process, while the female lecturer produced 665 fillers in the teaching process. Secondly, the data showed that both the female teacher and lecturer produced more unlexicalized than the lexicalized fillers. In the function of the fillers, the writer found that the types of fillers produced by both the female teacher and lecturer had the functions as a holder the turn, as a mark of hesitation, as empathizers, as time-creating devices, and as an editing term. As a conclusion, the writer concludes that the situation in the teaching process affects the types and the functions of the fillers.Â Key words: spoken discourse, classroom interaction, types and functions of fillers